Film geography: A new subfield - Lukinbeal, Chris; Zimmermann, Stefan (ERDKUNDE, 2006)
With this paper, we use the film The Day After Tomorrow to explore four future trajectories of film geography research. The first, geopolitics, examines how film images and narratives constitute shifting eddies within a larger geopolitical imaginary. The second, cultural politics, positions film as an arena in which social-spatial meaning is defined, contested and negotiated. The third, globalization, situates film under the rubric cultural industry. As a cultural industry, film is engaged in the spaces of flows, in that cultural meaning has been commodified for global consumption. The fourth trajectory of film geography research, science, representation and mimesis, examines the role of film in terms of the crisis of representation, realism, ideology and power.